Towards an understanding of behavioural intention to use online journalism - Varzandeh, Somayyeh; Abu Hassan, Musa; Hassan, Salleh; Hassan, Hamisah Zahra (Faculty of Modern Languages and Communication, University of Putra, 2014)
Online journalism as a new medium has challenged the meaning of the production capacity, policy, independency, difference of time and place, and in particular, the interaction between journalists and their audiences. The purpose of this study is to identify the factors that determine the intention to adopt online journalism by journalists in Iran, using a research model based on the Decomposed Theory of Planned Behaviour (DTPB). DTPB is one of the models developed by Taylor and Todd (1995a) to recognise particular salient beliefs by examining three factors, namely; attitude, subjective norm and perceived behavioural control that can influence the intention to use technology.